Health Information Seeking Among University Students Before and During the Corona Crisis—Findings From Germany - Schäfer, Markus; Stark, Birgit; Werner, Antonia M.; Tibubos, Ana Nanette; Reichel, Jennifer L.; Pfirrmann, Daniel; Edelmann, Dennis; Heller, Sebastian; Mülder, Lina Marie; Rigotti, Thomas; Letzel, Stephan; Dietz, Pavel (Frontiers in Public Health, 2021)
Health information-seeking behavior is the process of gathering information about health and disease and can be influential for health-related perception and behavior. University students are an important target group for prevention and health promotion and largely belong to an age group that is considered to play a leading role in propagating the SARS-CoV-2 epidemic in Germany. The paper deals with students’ health information-seeking behavior before and during the corona crisis, aiming to give insights into its determinants and implications. Using the example of a large German comprehensive university and based on two cross-sectional surveys in the summer of 2019 (n = 4,351) and 2020 (n = 2,788), we investigate which information channels students use for health information, how information-seeking changes during the course of the pandemic, and to what extent information-seeking is associated with risk perception and risk behavior. For a sub-sample of participants that participated in both surveys (n = 443), we also trace developments at the individual level through a longitudinal analysis. The results show that students’ health information-seeking takes place primarily online and changed markedly during the corona crisis. The comparatively high relevance of sources that are largely based on unchecked user-generated content raises the concern whether students’ health information-seeking behavior guarantees the necessary quality and reliability of health information. Significant correlations between the intensity of corona-related information seeking, risk perception, and actual risk behavior were found.